CONCENTRATION OF CLOVE POWDER (Syzygium aromaticum) IN MEAT SLINING AND ITS EFFECT ON BROILER MEAT CHARACTERISTICS - M.L., BERAHUN; LINDAWATI, S. A.; MIWADA, I N. S. (Majalah Ilmiah Peternakan, 2022)
This study aims to determine the concentration of clove powder (Syzygium aromaticum) in meat slimming and the effect of the characteristics of broiler meat. The research was conducted in November 2019 - January 2020 at the Laboratory of Animal Product Technology and Microbiology, Faculty of Animal Husbandry, Udayana University. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. The four treatments were: (P0) chicken meat without clove powder coating, (P1) chicken meat coated with 0,25% clove pow- der, (P2) chicken meat coated with 0,50% clove powder, (P3) chicken meat coated with powder cloves 0,75%. The variables observed were pH , water content, water binding capacity and total bacteria. The results showed that the broiler meat coated with clove powder in treatment P0, P1, P2, and P3 obtained pH of 5,04 - 4,83; moisture content 68,97% - 74,45%; water holding capacity 67,90% - 69,16%; and total bacteria 5,00x106cfu/g – 2,00x104cfu/g. The conclusion of this study indicated that clove powder with a concentration of 0,75% was able to be a natural preser- vative for broiler meat with a characteristic pH 4,83; water content 74,45%; water holding capacity 69,16%; and total bacteria 2,00x104cfu/g.